If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 7) = 5(x + -7) + x Reorder the terms: 6(7 + x) = 5(x + -7) + x (7 * 6 + x * 6) = 5(x + -7) + x (42 + 6x) = 5(x + -7) + x Reorder the terms: 42 + 6x = 5(-7 + x) + x 42 + 6x = (-7 * 5 + x * 5) + x 42 + 6x = (-35 + 5x) + x Combine like terms: 5x + x = 6x 42 + 6x = -35 + 6x Add '-6x' to each side of the equation. 42 + 6x + -6x = -35 + 6x + -6x Combine like terms: 6x + -6x = 0 42 + 0 = -35 + 6x + -6x 42 = -35 + 6x + -6x Combine like terms: 6x + -6x = 0 42 = -35 + 0 42 = -35 Solving 42 = -35 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3x+2x+10=5x+5 | | 11x^2+30x-9=0 | | 6(x-9)x=7(x-8)+2 | | 5(3a-b)-7(3b-7a)= | | 9x+7y=-70 | | 3x+2x+10=5x+1 | | 8m(m+3)=2m-5 | | -4/5t+2/5=2/3 | | 4x-2(x-5)=2(x+1)+9 | | 9x+3-3x-5=30 | | 9y+9=45 | | 2y+3(y-4)=6y-3(y-10) | | -5(y-4)=40 | | 192z^2-20x-2=0 | | 7x-5+2x=3+4x+12 | | 4y+4(y-8)=8y-2(y-10) | | x(x-2y)-6= | | 9x^2+486=0 | | 15x^2-41x+22=0 | | 4(-1+-2y)-4y=20 | | -3(2m-2)-2(m+2)= | | 3(4x+1)=6(2x+1) | | 3y-13y-17=13 | | 7x-2(x-8)=5(x+1)+7 | | 6x+9+2x=y | | 25=0.5x | | 3a+4=12 | | 2(3x+1)=6x-1 | | 3a+4a=17 | | 17.5=2(2w)+2w | | 1760=0.05x | | 1x+4y=-3 |